Induction of leg-shaking, knock-down and killing responses by gamma-ray irradiation in Shaker mutants of Drosophila melanogaster. - Megumi, T.; Gamo, S.; Ohonishi, T.; Tanaka, Y. (Journal of Radiation Research, 1995)
Induction of membrane-associated responses, a leg-shaking, a knock-down and a killing, by gamma-ray irradiation was investigated in Shaker (Sh) mutants of Drosophila melanogaster in which the gene cords for the A-current K+ channel. Sh mutants were more sensitive in the knock-down response after gamma-ray irradiation than wild types. There were a great amount of sex difference in the knock-down response, males being more sensitive than females, but not in the killing response. The sex difference was larger than gene dosage effect on X chromosome in females. Genetical analysis revealed that the sensitivity of the knock-down response is an incompletely dominant character without maternal effects. The leg-shaking response, which had previously been reported to be induced by ether treatment, was demonstrated in the head-removed flies of Sh mutants. It was found to be the most sensitive among the responses tested, and may involve changes in K+ channel. The knock-down response may be related to expansion of the leg-shaking response. The killing response should have causes different from the leg-shaking and the knock-down responses judging from the lack of correlation with them.